The status of Circassian princes in the 17th century: Independent Inaledes - F.A. Ozova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The research on the well-known Ottoman sources, “The Book of Travels” by Evliya Çelebi and “Stating the Essence of Laws of the Ottoman Dynasty” by Husen Hesarfen, shows that their data have not been introduced into the scientific use. However, these data are unique with regard to the political history of Circassia in the 17th century, which was a decentralized monarchy of representatives of nobility in the form of a federative princely republic. The data obtained from the Ottoman, Russian, and European sources allow to analyze the status of the representatives of the ruling princely dynasty of Inaledes in Circassia, as well as to disclose the international and legal status acquired by them in the 17th century. The paper is devoted to the analysis of the Ottoman-Circassian-Crimean relations in the light of the Ottoman doctrine that connected the confessional supremacy with the military and political one. It has been revealed that the relations in the military and political spheres played the key role in contrast to the confessional ones. This conclusion is confirmed by the facts of a fierce confrontation between the most early Islamized territories of Circassia, including Kabarda, Bzhedugia, Besleney, Hatukai, and Zhaney, and the Ottoman-Crimean coalition, despite they must have been regarded to as “countries of Islam” (dar al-islam) according to their political rhetoric. In that period, the Ottoman-Crimean coalition demanded mostly a military alliance following the adoption of the Islamic faith as their official religion, whereas the Inaledes refused to accept the fact that the religious community should grant any military, political, and economical rights to sultans and Crimean khans in Circassia. Such discrimination between the confessional and military-political factors shows that the military-political aspect played a more important role in the relations with the Circassians than the confessional one for the Ottoman-Crimean coalition in the Caucasus. This is precisely why the whole territory of Circassia in the 17th century, excluding that of the Zhaney (some of its princes had suzerain-vassal relationships, while the other ones were allies), was a “country of war” (dar al-harb).